Astra zeneca Covid vaccination conversion reaction - Roy G Beran (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Introduction: This paper reports a patient who presented with hemiparesis and hemisensory hypo-aesthesia following the AstraZeneca vaccine. Formal neurological assessment diagnosed a conversion reaction. Case report: A 60 year old lady presented with left sided weakness and hypo-aesthesia after her first dose of the AstraZeneca vaccine. She became unable to walk, had blurred vision and a bitter taste. There was no similar previous history. Depression and anxiety were diagnosed in 2007. Physical examination revealed positive Hoover's signs, without features to suggest either upper or lower motor neurone deficit. She had non-anatomic loss of sensation, across her torso, plus non-anatomical demarcation of decreased trigeminal sensation.  She was advised that her most likely diagnosis was that of a non-organic conversion reaction but she did undergo cerebral imaging together with a psychiatric assessment, prior to discharge.  Discussion: The AstraZeneca Covid-19 vaccine has received significant publicity regarding potential for clotting. This case highlights the consequences of this concern. Physical examination suggested a non-organic complaint, allowing the provisional diagnosis of a conversion reaction.  Advising the patient allowed her to accept that, when all the tests came back normal, it did not reflect lack of knowledge to make a correct diagnosis. The correct procedure is to make a provisional diagnosis (namely conversion reaction) and to exclude differential diagnoses, such as clotting. It is believed that this represents the first reported case of an AstraZeneca Covid vaccination conversion reaction but it is highly unlikely that it will be the last one to be encountered.